Ethical leadership - Ashman, Ian (Henry Stewart Talks, 2011)
Defining leadership and ethics, Conventional wisdom on ethical leadership, Key moral philosophies and their application to leadership (Machiavelli; deontology; utilitarianism; virtue), An existentialist critique, A case study and conclusions
Reviewed at 2018/10/28